Role of Monks Affecting Social and Community Development Case Study Thai Chumpon Temple Muang District Sukhothai - Nissabho , PhrakhruPalad Somchai; Wongsawad , Thutsapong; Hassarin , Prasong (Journal of Modern Learning Development, 2020)
The purpose of this research is 1. To study the role of monks in social and community development Case Study Thai Chumpon Temple, Muang District, Sukhothai, 2. study problems and obstacles to the implementation of the role of monks in social and community development, The population used in the research was people living in Thani Sub-District Municipality, Muang District, Sukhothai Province, totaling 1,940 people. The sample size was 322 samples by stratified randomization. The research tool was closed-ended questionnaire the statistics used in the research were descriptive statistics, percentage, mean and standard deviation. The results study revealed that 1) Most of respondents were male, aged 18-39, educated at lower than bachelor’s degree, average monthly income 10,001-15,000 baht and has self-employed. 2) The results of the role the monks social and community development, the overall average high, ranked from descending order including activities between monks and communities in the propagation of dharma and spiritual development and community support, 3) Problems and obstacles to the implementation of the role showed that people with low economy were problem for the monks and novices. The Buddhism Office should provide budget to help monks and novices, lack of monks with managerial abilities there should be training for the monks on temple management, or bring the monk at the abbot level to study and visit the sample development temple.